The Effect of Moringa Leaf Decoction on Breast Milk Production and Hemoglobin Levels in Postpartum Mothers at Juliana Clinic Tanjung Morawa in 2023 - Mayang Citra Hariati; Irma Nurianti; Putri Amanda (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Moringa leaves (Moringa oleifera) are functional plants with an abundance of nutrients both macronutrients and micronutrients. The need for nutrition in postpartum and lactating mothers is more than the nutritional needs of mothers during pregnancy, during the first 6 months the mother needs an additional energy of 500 calories / day which is useful for producing adequate milk production for the baby. The use of Moringa leaves has been widely used by the community as an alternative menu that is beneficial for mothers during pregnancy and breastfeeding mothers. For postpartum and lactating mothers, Moringa leaves are very useful and contain phytosterol compounds that are lactagogum effects that can increase and launch milk production so that they can improve the baby's health status by increasing the baby's weight and can also prevent stunting in infants. This research is a Quasy Experiment research with One Group Pretest and Postest Design approach. The sample in this study was determined by Purposive Sampling technique, which is a sample with a total of 19 postpartum mothers at the Juliana Tanjung Morawa midwife clinic. The results of the study found a difference between before and after being given Moringa leaf boiled water on maternal breast milk production, this can be seen from the sig value of 0.000 and the difference between before and after being given Moringa leaf cooking water on maternal HB levels, this can be seen from the GIS value of 0.000, it was concluded that there was an effect of Moringa leaf cooking water on breast milk production and Hb levels of postpartum mothers at the Juliana Tanjung Morawa clinic.